Computation of block error rates with randomly varying block sizes. - Abaya, Efren F. (Philippine Engineering Journal)
The block error rate (BLER) is a basic parameter of data communication channels which is usually computed on the assumption of independent and identically distributed bit errors and fixed block sizes. This paper presents a method of computing block error rates when the block sizes are allowed to vary according to a known probability distribution. It is shown that under some simple conditions the block error rate is relatively insensitive to the actual distribution or to the variance of the block length, and that it depends largely on the average block length. Some analytic and numerical computations are presented to illustrate the method.